Long‐Term Therapy With Teduglutide in Parenteral Support–Dependent Patients With Short Bowel Syndrome: A Case Series. Issue 4 (30th March 2018) - Ukleja, Andrew; To, Chau; Alvarez, Alicia; Lara, Luis F.
Abstract: Objective: To review all cases of parenteral support (PS)–dependent patients with short bowel syndrome (SBS) treated with teduglutide (Gattex, Shire) and to evaluate its efficacy and adverse effects. Methods: This is a retrospective descriptive cohort of SBS patients treated with teduglutide. Demographics, bowel length, primary diagnosis, PS volume/duration, teduglutide dose, and side effects were collected prospectively. Results: Six SBS patients (4 females, 2 males) received teduglutide. Mean age was 46.3 years (range 26–71). SBS etiology was vascular (n = 3), multiple resections (n = 2), and strangulation (n = 1). Length of residual small bowel was between 30–120 cm. The bowel anatomy was colon present (n = 3) and stoma n = 3 (ileostomy, 2; colostomy, 1). PS duration was 1.5–14 years. Weekly PS volume was mean 7.7 liters/week (1–14). Number of PS days per week ranged 1–7 days. Mean duration of teduglutide therapy was 31 months (24–36). All patients achieved ≥20% reduction in PS weekly volume within 6 months. PS was weaned in all patients. Adverse effects included abdominal bloat/discomfort (n = 3), stoma enlargement (n = 3), bowel obstruction (n = 1), and congestive heart failure (n = 1). Conclusions: All PS‐dependent SBS patients treated with teduglutide were weaned off PS. Patients with colon in continuity and lower PS weekly volume requirements were weaned off PS sooner than those with end‐stomas and higher PS volume requirements. Teduglutide was well tolerated. Additional clinical studies of teduglutide in SBS patients with marginal PS requirements are needed.